Zapotecs on the Move : Cultural, Social, and Political Processes in Transnational Prespective - Cruz-Manjarrez, Adriana, 1966- (Latinidad: Transnational Cultures in the United States., 2013)
Through interviews with three generations of Yalálag Zapotecs ("Yalaltecos") in Los Angeles and Yalálag, Oaxaca, the author examines the impact of international migration on this community, tracing five decades of migration to Los Angeles to delineate migration patterns, community formation in Los Angeles, and the emergence of transnational identities of the first and second generations of Yalálag Zapotecs in the U.S.